CONTRIBUTION TO EXPERIMENTAL INVESTIGATION OF FITTING OF CALIBRATION CURVES OF CURRENT TRANSFORMERS - Juhas, Atila; Vujicic, Vladimir (Journal on Processing and Energy in Agriculture, 2021)
The paper experimentally investigates the problem of fitting calibration curves of current transformers (CT). An efficient fitting algorithm enables precise and accurate electronic online correction of CT errors and thus effective improvement of their accuracy class. The paper presents the results of one such algorithm which allows correcting the transformers current ratio error to the level of 0.004%. The base are 8 key calibration points in the range 1% ‑ 200% of the CT’s nominal primary current.
Keywords: curve fitting, calibration, accuracy class